PENGARUH INFLASI, EKSPOR DAN ANGKATAN KERJA TERHADAP PDB PERKAPITA DI INDONESIA - Salsabila, Vira; Murtala, Murtala (Jurnal Ekonomi Regional Unimal, 2024)
This research aims to determine the influence of inflation, exports and labor force on GDP per capita in Indonesia. This Research uses secondary data from 1996 to 2022. Data analysis method used is Auto Regressive Distributed Lag (ARDL) analysis. Partial research results shows that inflation has a negative and insignificant effect on Indonesia's GDP per capita, exports have a positive and significant effect on Indonesia's GDP per capita and the labor force has a positive and insignificant effect on Indonesia's GDP per capita. At the same time, inflation, exports and the labor force have a positive and significant effect on Indonesia's GDP per capita.